2012
DOI: 10.1051/0004-6361/201117849
|View full text |Cite
|
Sign up to set email alerts
|

A (sub)millimetre study of dense cores in Orion B9

Abstract: Context. Studies of dense molecular-cloud cores at (sub)millimetre wavelengths are needed to understand the early stages of star formation. Aims. We aim to further constrain the properties and evolutionary stages of dense cores in Orion B9. The prime objective of this study is to examine the dust emission of the cores near the peak of their spectral energy distributions, and to determine the degrees of CO depletion, deuterium fractionation, and ionisation. Methods. The central part of Orion B9 was mapped at 35… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 89 publications
(157 reference statements)
5
66
0
Order By: Relevance
“…The envelope as observed at 870 μm is extended to the east and at 350 μm there are a few sub-peaks associated with the extended 870 μm emission (Miettinen et al 2012). We do not, however, detect 2.9 mm continuum emission from these sub-peaks, indicating that they do not harbor compact protostellar sources.…”
Section: A4 090003mentioning
confidence: 96%
See 1 more Smart Citation
“…The envelope as observed at 870 μm is extended to the east and at 350 μm there are a few sub-peaks associated with the extended 870 μm emission (Miettinen et al 2012). We do not, however, detect 2.9 mm continuum emission from these sub-peaks, indicating that they do not harbor compact protostellar sources.…”
Section: A4 090003mentioning
confidence: 96%
“…Much like 093005, its only detection shortward of 24 μm is at 4.5 μm, where there is a small feature offset from the location of the protostar, indicative of shocked H 2 emission (Miettinen et al 2012;Stutz et al 2013).…”
Section: A4 090003mentioning
confidence: 98%
“…Using this temperature, the core mass was determined to be 7.8±1.6 M , and its volume-averaged H 2 number density was estimated to be 1.1 ± 0.2 × 10 5 cm −3 . In the SABOCA 350-μm mapping of Orion B9 by Miettinen et al (2012;Paper III), SMM 3 was found to be by far the strongest source in the mapped area (S 350 5.4 Jy). We also found that it contains two subfragments, or condensations (we called SMM 3b and 3c), lying about 36 −51 in projection from the central protostar.…”
Section: Introductionmentioning
confidence: 98%
“…+ (Miettinen et al 2012), NHD2 ; -towards low-mass and high-mass protostars: D2CO, HDCO (Bergman et al 2011), DCOOCH3 (Demyk et al 2010;Margulès et al 2010), HDO (Coutens et al 2012, D2O , OD (Parise et al 2012); -in protoplanetary disks: DCN, DCO + (van Dishoeck et al 2003;Guilloteau et al 2006;Qi et al 2008;Öberg et al 2015), N2D…”
Section: Introductionmentioning
confidence: 99%